2021
DOI: 10.3390/s21237852
|View full text |Cite
|
Sign up to set email alerts
|

A Domain-Independent Generative Adversarial Network for Activity Recognition Using WiFi CSI Data

Abstract: Over the past years, device-free sensing has received considerable attention due to its unobtrusiveness. In this regard, context recognition using WiFi Channel State Information (CSI) data has gained popularity, and various techniques have been proposed that combine unobtrusive sensing and deep learning to accurately detect various contexts ranging from human activities to gestures. However, research has shown that the performance of these techniques significantly degrades due to change in various factors incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…DMNet [19] and GNG [15] also utilized GAN to produce additional samples and facilitate activity recognition. A recent work [39] explored GAN to learn domain independent features for activity recognition. These prior works in essence exploit the data generation ability of GAN model to synthesize virtual samples in target domains and facilitate domain adaption.…”
Section: Gan-based Wifi Sensing Techniquesmentioning
confidence: 99%
“…DMNet [19] and GNG [15] also utilized GAN to produce additional samples and facilitate activity recognition. A recent work [39] explored GAN to learn domain independent features for activity recognition. These prior works in essence exploit the data generation ability of GAN model to synthesize virtual samples in target domains and facilitate domain adaption.…”
Section: Gan-based Wifi Sensing Techniquesmentioning
confidence: 99%
“…In the later or pre-implementation stage (in real-life settings), actors or PwDs can be invited for determinative performance analysis of the system. Along with that, this dataset opens new avenues for gaining insights into the ubiquitousness and domain-transfer applications of CSI-based sensing as it contains parameters like different activity locations, participant characteristics, and placement of Tx-Rx [211]. Insights into the ubiquitousness can help in making informed decisions on using these advanced sensing systems.…”
Section: Implications Of Wi-gitation Datasetmentioning
confidence: 97%
“…In a recent study, the problem of domain change due to environment and person was identified, and to mitigate that a domain-independent generative adversarial network was proposed and evaluated for gesture recognition [224].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations